Role Of Panchakarma In The Management Of Cerebral Palsy - Mishra, Jyoti; Verma, Mithilesh (International Research Journal of Ayurveda & Yoga, 2020)
Cerebral palsy is the leading cause of childhood disability affecting function and development of children. Cerebral palsy is non progressive irreversible disease of the central nervous system . Motor disorders of Cerebral palsy are accompanied by disturbances of sensation ,perception, cognition, communication and behavior. Children with Cerebral palsy affected exhibit impaired muscle coordination, decreased velocity, overactive reflexes, muscles contractures, altered biomechanics, disuse, sensory impairment, hypertonia etc. In Ayurveda there is no correlation with any single disease or condition. Cerebral palsy may be correlated with Janma Bala Pravritta Vyadhi or Shiro marmabhighata and Vata Vyadhi , beside these some symptoms like pangulya , muka, minmin & gadgad , badhirya ekangaroga ,sarvangaroga , pakshaghata , pakshavadha, vepathu, mukha vakrata ,hatekpaksh etc, are described as main symptoms of Vata Vyadhi. Various PANCHAKARMA PROCEDURES which are commonly used in Vata vyadhi like Udwartana , Sarvaang abhyanga , Shashtikshali pinda Sweda, Shirodhara , Nasya, Basti etc. are found to be beneficial in the management of Cerebral Palsy in Children. Udwartana is kapha, vata hara and removes srotash awarodha. Udwartana along with abhyang also open minute channel and improve blood as well as lymphatic circulation. Swedana reduces pain, spasticity, improve range of motion, flexibility of joint along with Snehana. Nasya is a therapeutic procedure which is used in various systemic diseases mainly for urdhavjatrugat bhaag. Shirodhara may modulate the secretions of various neurotransmiter at brain cellular level. Basti is best treatment to vitiated Vayu, it may destroy the seed of all disease , it improve gross as well as fine motor functions provide nourishment ,improve overall general condition .It is major general treatment for Cerebral palsy affected children.